COMMUNITY SERVICE LACK OF KNOWLEDGE LEVEL OF EXCLUSIVE BREASTFEEDING IN SIPULTAK DOLOK VILLAGE, PAGARAN DISTRICT WHOLESALE - Rizky Andriana Bakara; Emelia Tampubolon (Cattleya Darmaya Fortuna, 2023)
Exclusive breastfeeding during the first six months of life is a crucial step in fulfilling basic nutrition for children to reduce infant morbidity and mortality. However, the achievement of Exclusive Breastfeeding in Sipultak Dolok Village, Pagaran District, is still not optimal due to the low level of knowledge of breastfeeding mothers, the influence of cultural myths, and lack of access to accurate information. This community service activity aims to increase the understanding of breastfeeding mothers and families about lactation management and the importance of exclusive breastfeeding to support healthy child growth and development and prevent stunting. The intervention was carried out by a team from STIKes Darmo Medan through direct counseling and education methods to breastfeeding mothers and families in Sipultak Dolok Village on April 17, 2023. The results of the activity showed an increase in enthusiasm and understanding of the community after being given education. In conclusion, a structured educational approach is very effective in changing people's mindset to switch from the habit of early supplemental feeding to proper exclusive breastfeeding, in order to realize a quality generation.